2023
DOI: 10.2147/ijn.s431061
|View full text |Cite
|
Sign up to set email alerts
|

Potential Efficacy of Herbal Medicine-Derived Carbon Dots in the Treatment of Diseases: From Mechanism to Clinic

Mingtang Zeng,
Yao Wang,
Maozhu Liu
et al.

Abstract: Carbon dots (CDs), a crucial component of nanomaterials, are zero-dimensional nanomaterials with carbon as the backbone structure and smaller than 10 nm. Due to their beneficial characteristics, they are widely used in biomedical fields such as biosensors, drug delivery, bio-imaging, and interactions with DNA. Interestingly, a novel type of carbon dot, generated by using herbal medicines as synthetic raw materials, has emerged as the most recent incomer in the family of CDs with the extensive growth in the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 113 publications
0
1
0
Order By: Relevance
“…However, most CDs are chemically synthesized derivatives using multiple materials which biocompatibility and biological security falls short of that of natural sources. [39][40][41] Moutan Cortex (MC), a well-known Traditional Chinese Medicine, has a long history of medical applications in China and other Asian countries. Modern studies have shown that MC has antioxidant, anti-cancer, hypoglycemic, anti-aggregatory, anti-inflammatory, and antiallergic properties, and other effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, most CDs are chemically synthesized derivatives using multiple materials which biocompatibility and biological security falls short of that of natural sources. [39][40][41] Moutan Cortex (MC), a well-known Traditional Chinese Medicine, has a long history of medical applications in China and other Asian countries. Modern studies have shown that MC has antioxidant, anti-cancer, hypoglycemic, anti-aggregatory, anti-inflammatory, and antiallergic properties, and other effects.…”
Section: Introductionmentioning
confidence: 99%